Psychosocial Impacts on Pentecostal Church Pastors of Providing Support to Children in Need of Care and Protection: An Interpretative Phenomenological Analysis Design - Spaumer, Andrew (Pastoral psychology, 2025)
Pentecostal church pastors are engaged in supporting children in need of care and protection. This study employed an interpretative phenomenological analysis design to explore the psychological impacts on pastors of Pentecostal churches supporting children in need of care and protection. The study was conducted in South Africa with 19 criterion purposively selected Pentecostal church pastors. Semistructured face-to-face interviews were conducted. Data were analyzed thematically, guided by the interpretative phenomenological analysis framework. The trustworthiness of the study was established through adherence to credibility, transferability, dependability, and confirmability. Findings indicate that Pentecostal church pastors derive satisfaction and happiness from providing care and support to children in need of care and protection. However, their inability to provide the requisite support results in feelings of sadness and disappointment. The provision of care and support to children encroaches upon the Pentecostal church pastors’ family time and occasionally necessitates the utilization of family resources to deliver the required assistance. The assistance offered by Pentecostal church pastors to children in need of care and protection is accompanied by conflicting emotions of both satisfaction and emotional distress. Researchers recommend collaborative efforts between child protection practitioners, such as social workers and Pentecostal church pastors, to enhance support for children in need of care while maintaining their health and families.